The Nature of Educators and Students: The Study of Islamic Education Philosophy towards Character Establishment - Abdul Muis (Universitas Muhammadiyah Malang, 2021)
Teachers are referred to as educators who have expertise and experience in education, which must have a good personality and good speech. Educators have a huge responsibility because educators must guide and direct students to become individuals of good character. Students have varied characteristics who need guidance from an educator so that their potential can develop appropriately by the characters developed in the educational environment. The purpose of this study is to find out and apply the nature of educators and students according to Islam and how strategies shape students' character. The scientific approach used is the study of the philosophy of Islamic education in character building. The research method is qualitative - literature study or library research by reviewing the literature on character deepening. The focus of the discussion of this paper is on the nature of educators and students, the duties and roles of educators, and the character of an educator and student from the perspective of Islamic philosophy.